CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI MEDIATOR DALAM HUBUNGAN GREEN ACCOUNTING DAN PROFITABILITAS PADA PERUSAHAAN ENERGI DI INDONESIA - Kirana Yasmine; Imam Ghozali (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of green accounting on profitability, the effect of green accounting on Corporate Social Responsibility (CSR), the effect of CSR on profitability, and the mediating role of CSR in the relationship between green accounting and profitability in energy companies in Indonesia. The increasing demand for sustainability practices and Environmental, Social, and Governance (ESG) transparency has encouraged energy companies to integrate environmental and social aspects into their business strategies. This study employed a quantitative approach using secondary data obtained from annual reports, sustainability reports, Bloomberg databases, and PROPER data from energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Purposive sampling was used to select 13 companies with a total of 43 observations. Green accounting was measured using PROPER scores, CSR using Social Disclosure Score, and profitability using Return on Assets (ROA). The data were analyzed using multiple linear regression and Sobel test. The results indicate that green accounting has no significant effect on profitability but positively affects CSR. CSR positively influences profitability. However, CSR does not mediate the relationship between green accounting and profitability. These findings suggest that sustainability practices in energy companies provide long-term benefits through enhanced legitimacy and stakeholder trust rather than direct financial gains.